Decellularized pericardium tissues at increasing glucose, galactose and ribose concentrations and at different time points studied using scanning X-ray microscopy. (2021) - Giannini, Cinzia; Caro, Liberato De; Terzi, Alberta; Fusaro, Luca; Altamura, Davide; Diaz, Ana; Lassandro, Rocco; Boccafoschia, Francesca; Bunk, Oliver
No abstract available